Carl Schmitt’s Legal Fascism - Ohana, David (Politics, religion & ideology, 2019)
Carl Schmitt, the supreme jurist of the Third Reich, bestowed legal legitimacy on Hitler's dictatorial rule. A genealogy of his primary writings of the German jurist shows that his romance with the Nazis was not the result of an historical accident, and proves that there is a thread running from his early theoretical writings to his juridical position and his radical political activity during the thirties. Schmitt is a member of the ‘nihilist order’—thinkers, artists and cultural critics who promogulated the nihilistic position which at the same time was a dynamic structure on a totalitarian basis. The members of the ‘nihilist order’ generally moved from nihilistic criticism to totalitarian conclusions. Schmitt, on the other hand, took the opposite route—from totalitarianism to nihilism.